Analisis Minat dan Risiko Dalam Penggunaan Whaff Reward Menggunakan Model Technology Acceptance Model (TAM) - Richie Mahfud Ahmed Sambora; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The difficulty of getting a job is no longer a new problem for the public, especially Indonesian citizens. The rapidly evolving technology has allowed the public to open their horizons to search for grains of income on the internet. One of them by using Whaff Reward. Of the approximately 10,000,000 users are already using Whaff Reward (Android Playstore, 2017). Whaff Reward is an advertising medium as well as Paid per Download application with a segment of developers and users of Whaff Reward itself. Among the many attacks on the security sistem e-money it will trigger user worries Whaff Reward application. In this study, researchers conducted a parametric analysis to determine what faktors make Whaff Reward users in Indonesia using Whaff Reward. By combining several models of Technology Acceptance Model (TAM), Trust, Perceived Risk and Theory of Planned Behavior (TPB). Collection of sample data by using questionnaire and analyzed by Linear Regression method. The number of samples used in this study amounted to 154 data. The results of this study show that users in Indonesia use Whaff Reward because they feel they have perceived results, benefit themselves, the influence of the nearest people, the available infrastructure, the feeling of trust in the organization's commitment, the good reputation of the organization and the experience positive results obtained when using Whaff Reward